Antecedents of intention to return home and moderating effects of initial return intention among Iranian students in Malaysia - Rahnamafard, Najmossadat (2012)
With the recent development of globalization, the population of international students has reached 2.7 million globally in 2004 (Hughes, 2008). Advantage of study abroad is to improve students’ abilities and skills toward international competence. However, disadvantage of study abroad is to reduce the possibility of returning to home after graduation (Chen & Su, 1995). In the context of Iran, Fekrazad, (2010), confirmed that the determinants of emigration (initial nonreturn intention) overlap the determinants of studying abroad (initial return intention). Therefore, this study was designed to predict intention to return home after graduation and to determine moderating effect of initial return intention among Iranian students in Malaysia. The present study focused on the theory of planned behavior model by considering psychological characteristics; attitude, subjective norm and perceived behavioral control in intention to return home. This study also designed to increase the predictive validity of the theory of planned behavior by applying initial return intention before leaving home that might moderate the relationship between two components of planned behavioral theory and return intention. In order to achieve to these goals, a cross sectional survey was utilized. The data were gathered by using a set of questionnaire through face to face contact with 346 Iranian students who were a stratified random sample selected from fourteen public and private Malaysian universities during May-July, 2011.Descriptive statistics was used to provide a better understanding of socio demographic characteristics of students, level of attitude toward return home, subjective norm to return home and perceived behavioral control over return home. Confirmatory Factor Analysis (CFA) was used to examine construct validity and reliability of the model. Structural Equation Model was a statistical model used to predict the return intention to home and finally Multigroup SEM was selected to test the moderating effects of ‘initial return intention between two predictors (attitude, subjective norms) and return intention. The findings of study showed that on average, attitude, subjective norm, and perceived behavioral control explained 70% of the variance of return intention. The level of return intention, attitude toward return home and subjective norm was relatively moderate while the level of perceived behavioral control was low. The relationship between three predictors and return intention was positive, moderate and significant at the 0.01 level. Further, initial return intention moderated the effects of attitude and subjective norm on return intention. Therefore, the conceptual model developed for this study was able to predict return intention among Iranian students from their attitude, subjective norms and perceived behavioral control. In addition, the present study demonstrated that initial return intention has moderating effect on attitude–intention and subjective norm –intention relations. This study recommends attitude, subjective norms and perceived behavioral control is appropriate to predict return intention to home; however, to understand the underling determinants of these predictors, behavioral, normative, and control beliefs should be assessed. Moreover some recommendations for policy and practice were suggested to facilitate returning to home by making more opportunities for young people in Iran. This study also highlighted the need for future research on return intention from study abroad by considering other factors among other international students.